Evidências experimentais para a associação entre o nível de relação filogenética e a intensidade de competição entre espécies de gramíneas exóticas e nativa - AZEVEDO, Rodrigo Carvalho de (2009)
Biological invasions has been a major threat to whole biomes around the world, affecting communities and ecossistems with consequences to the trophic web. At the same time it is a huge biogeographical experiment that allows the formulation of hypotheses about the rules for communitie assembly. This study tested the hypothesis that the level of phylogenetic relationship is positively correlated with the magnitude of competitive interactions, being stronger for closer species. We used two exotic African species (Panicum maximum and Andropogon gayanus) and a native of South America (Paspalum atratum-focal species) in a partial additive design for the mix of native-exotic, with an increase in density of the exotic. The results showed greater competitive effect on the focal species when in the presence of P. maximum (closer to the focal), suggesting that predictions can be made on potential invasive species based on the Darwin s Naturalization Hypothesys.